The Falkland Islands Dependencies Survey, 1947–50 - Fuchs, V. E. (Polar Record, 1951)
Since the description of the activities of the Falkland Islands Dependencies Survey for 1946–47 by Surgeon-Commander E. W. Bingham no general account of the Survey's activities has appeared in the Polar Record . The writer's connection with these activities dates from 1948, but in order to bring the story up to date, it is necessary to begin in 1947.